The Multimodal Nature of High-Intensity Functional Training: Potential Applications to Improve Sport Performance - Joao Henrique Falk Neto; Michael D. Kennedy (MDPI AG, 2019)
Training for sports performance requires the development of multiple fitness components within the same program. In this context, training strategies that have the potential to concomitantly enhance metabolic and musculoskeletal fitness are of great value for athletes and coaches. The purpose of this manuscript is to review the current studies on high-intensity functional training (HIFT) and to assess how HIFT could be utilized in order to improve sport-specific performance. Studies on untrained and recreationally-active participants have led to positive results on aerobic power and anaerobic capacity, and muscular endurance, while results on muscular strength and power are less clear. Still, HIFT sessions can elicit high levels of metabolic stress and resistance training exercises are prescribed with parameters that can lead to improvements in muscular endurance, hypertrophy, strength, and power. As similar training interventions have been shown to be effective in the athletic population, it is possible that HIFT could be a time-efficient training intervention that can positively impact athletes' performances. While the potential for improvements in fitness and performance with HIFT is promising, there is a clear need for controlled studies that employ this training strategy in athletes in order to assess its effectiveness in this population.